Force model for impact cutting grinding with a flexible robotic tool holder. Issue 1 (July 2016) - Tahvilian, Amir; Hazel, Bruce; Rafieian, Farzad; Liu, Zhaoheng; Champliaud, Henri
Abstract Traditionally, grinding is used as a finishing process in the manufacturing chain. However, in recent years, it has been also used to machine hard or brittle materials. Another application, developed by Hydro-Québec's research institute, IREQ, is robotic grinding for in situ maintenance of large hydropower equipment. This high material removal rate grinding process is performed with a flexible robot as the tool holder. In a robotic grinding process, having an accurate model to predict the process force is crucial in order to achieve the desired material removal rate. This paper presents an experimental study that breaks new ground in determining the coefficients of an existing semi-analytical force model. An impact cutting behavior has been clearly observed at various grinding power levels both with high-speed video and force-measuring equipment. The force model is based on an idealized uncut chip at each wheel impact on the surface. The number of impacts per revolution of the grinding wheel is ascertained and used to determine the coefficients of the force model. The previously determined energy partition ratios and correlated model are also used to determine the ratio of energy consumption through friction to that for chip formation. The force coefficients are then fine-tuned and updated using the energy partition model and friction-chip energy ratio for the process. The newly determined coefficients are validated through a series of tests and shown to be in good agreement with measured grinding forces. The results show that the new enhancements in determining model parameters can be used to better predict the process force, power, and depth of cut in different cutting regimes and at various grinding power levels.